TIM-3 in Leukemia; Immune Response and Beyond - Rezaei, Mahnaz; Tan, Jiaxiong; Zeng, Chengwu; Li, Yangqiu; Ganjalikhani-Hakemi, Mazdak (Frontiers in Oncology, 2021)
T cell immunoglobulin and mucin domain 3 (TIM-3) expression on malignant cells has been reported in some leukemias. In myelodysplastic syndrome (MDS), increased TIM-3 expression on TH1 cells, regulatory T cells, CD8+ T cells, and hematopoietic stem cells (HSCs), which play a role in the proliferation of blasts and induction of immune escape, has been reported. In AML, several studies have reported overexpression of TIM-3 on leukemia stem cells (LSCs) but not on healthy HSCs. Overexpression of TIM-3 on exhausted CD4+ and CD8+ T cells and leukemic cells in CML, ALL, and CLL patients could be a prognostic risk factor for poor therapeutic response and relapse in patients. Currently, several TIM-3 inhibitors are used in clinical trials for leukemias, and some have shown encouraging response rates for MDS and AML treatment. For AML immunotherapy, blockade TIM-3 may have dual effects: directly inhibiting AML cell proliferation and restoring T cell function. However, blockade of PD-1 and TIM-3 fails to restore the function of exhausted CD8+ T cells in the early clinical stages of CLL, indicating that the effects of TIM-3 blockade may be different in AML and other leukemias. Thus, further studies are required to evaluate the efficacy of TIM-3 inhibitors in different types and stages of leukemia. In this review, we summarize the biological functions of TIM-3 and its contribution as it relates to leukemias. We also discuss the effects of TIM-3 blockade in hematological malignancies and clinical trials of TIM-3 for leukemia therapy.